Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Himpunan Dengan Model Pembelajaran Reciprocal Teaching - eka suryani Rindani; adek nila sari harahap; Nurdalilah (JURNAL CERMATIKA, 2023)
This research is classroom action research (PTK). The learning tools used in this research are the Learning Implementation Plan (RPP), Student Activity Sheet (LAS), test instruments, student activity observation sheets and teacher ability observation sheets to manage learning. The results of the research showed that by applying the Reciprocal Teaching learning model in cycle I, the percentage of completeness in the minimum "sufficient" category was 73.08% and in cycle II it was 84.62%. There was an increase from cycle I to cycle II of 11.54%. With achievement indicators ≥ 80% have been achieved. Then, for the results of observations of student activities in cycle I, it was found that the level of student activity was 71.05% "fair" in cycle II 80.69% "good". The increase that occurred from cycle I to cycle II was 9.64%, the achievement indicator was ≥ 80%. Meanwhile, the results of observations of the teacher's ability to manage learning in cycle I and cycle II were obtained in the "good" category.